Function and therapeutic value of astrocytes in neurological diseases - Lee, Hong-Gyun; Wheeler, Michael A; Quintana, Francisco J (Nature reviews. Drug discovery, 2022)
Astrocytes are abundant glial cells in the central nervous system (CNS) that perform diverse functions in health and disease. Astrocyte dysfunction is found in numerous diseases, including multiple sclerosis, Alzheimer disease, Parkinson disease, Huntington disease and neuropsychiatric disorders. Astrocytes regulate glutamate and ion homeostasis, cholesterol and sphingolipid metabolism and respond to environmental factors, all of which have been implicated in neurological diseases. Astrocytes also exhibit significant heterogeneity, driven by developmental programmes and stimulus-specific cellular responses controlled by CNS location, cell-cell interactions and other mechanisms. In this Review, we highlight general mechanisms of astrocyte regulation and their potential as therapeutic targets, including drugs that alter astrocyte metabolism, and therapies that target transporters and receptors on astrocytes. Emerging ideas, such as engineered probiotics and glia-to-neuron conversion therapies, are also discussed. We further propose a concise nomenclature for astrocyte subsets that we use to highlight the roles of astrocytes and specific subsets in neurological diseases.